(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
A field experiment was conducted on Non-Calcareous Dark Grey Floodplain Soil to find out the performance of three mustard varieties viz., i) BARI Sarisha-9, ii) BARI Sarisha-12 and iii) Tori-7 (Local) and three fertilizer doses as : F1= 120-34-64-32-1.5 kg/ha NPKSB (HYG), F2 = 86-26-44-26-1.0 kg/ha NPKSB (MYG) and F3 = 54-60- 15 kg/ha NPK. The variety BARI sarisha-9 produced the highest seed yield (892 kg/ha). The fertilizer level of HYG gave higher seed yield (956 kg/ha). BARI Sharisha-9 gave higher gross return (Tk. 21882/ha) and gross margin (Tk.14936/ha) under HYG fertilizer level but higher BCR (3.54) was recorded under MYG fertilizer level due to less fertilization cost. Key words: Mustard, Variety, Fertilizer, Yield, Economics. Bangladesh J. Sci. Ind. Res. 42(3), 335-340, 2007